PENGARUH PERBANDINGAN KOMPOSISI TERHADAP ANGKA KONDUKTIVITAS TERMAL PAPAN PARTIKEL CAMPURAN SEKAM PADI DENGAN TIGA JENIS SERBUK KAYU - Wibowo, Hary; Nugroho, Lilik Cahyo (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2013)
Rice husk and wood sawdust produced in many parts of Indonesia as forest and agricultural waste. Both of these types of waste materials that can potentially be improved benefits and economic value, one way to be further processed into particle board. Particle board from a mixture of rice husk and sawdust than required strength properties, it is also necessary to study the nature of the heat transfer capability The purpose of this study to determine the value of the thermal conductivity of a mixture of rice husk particle board with three types of sawn wood dust. Three kinds of powder sawdust wood is teak, mahogany wood powder, sawdust and coconut. The study was conducted by means of modifications based on ASTM C177. Test particle board made ​​from a mixture of rice hulls - three types of wood dust by weight of the composition of each mixture 1:1, 2:1, 4:1 and 3:1 with density. The results showed that the rate of thermal conductivity (k) of the lowest 0.997 W / m ° C obtained in a mixture of rice husk particle board with teak wood powder with 1:1 composition. While the largest numbers conductivity obtained in a mixture of rice husk particle board - sawdust coconut (glugu) of 1.315 W / m ° C with a 2:1 composition.